The reliability of geochemical and isotopic data acquired at the metal-free chemical clean room and LA-MC-ICP-MS system of the institute of geological sciences, VAST - Tran, Tuan Anh; Nguyen, Hoang; Le, Duc Luong; Tran, Thi Huong; Cu, Sy Thang; Pham, Ngoc Can (Vietnam Journal of Science and Technology, 2025)
The newly constructed ISO5-class metal-free chemical clean room at the Institute of Geological Sciences requires verification for its cleanliness standards, while the recently installed Laser Ablation system, integrated with a Multi-Collector Inductively Coupled Plasma Mass Spectrometry (LA-MC-ICP-MS), must be certified for its analytical precision and accuracy before operational use. To assess both the clean room and the mass spectrometry system's reliability, a set of radiogenic isotope and geological reference samples was processed through chemical chromatography and mass spectrometry, with intercalated blanks included for control. The reference samples used in the evaluation included magmatic standards JA-2 and JB-1a from the Geological Survey of Japan, as well as radiogenic isotope solutions for Sr (NIST987), Nd (JNdi-1), Pb (NIST981), and Hf (JMC475). Trace element compositions were analyzed using a Quadrupole ICP-MS (Q-ICP-MS), while isotopic ratios were measured via MC-ICP-MS at both the Department of Physics and Earth Sciences, University of the Ryukyus (Okinawa, Japan), and the Institute of Geological Sciences (IGS). Results from both laboratories were compared to evaluate repeatability and accuracy, thereby providing a comprehensive assessment of the analytical reliability of IGS's facilities.